Adolescents with learning disabilities: Self-evaluation and social support - Skerytė-Kazlauskienė, Monika; Barkauskienė, Rasa (Psichologija, 2010)
Although learning disability (LD) has a primary impact on academic achievement, its relation to problematic social and emotional life of children and adolescents has been well recognised. In addition, attention has been paid to self-evaluation of schoolchildren with LD; however, the results of studies are contradictory and can be attributed to various factors. This paper seeks to shed light on the association between self-evaluation and perceived social support in adolescents with LD. We used the multidimensional model of Susan Harter (1999) for understanding and measuring the global and domain-specific self-evaluations. The goals of the current study were to assess relations of self-evaluation to the perceived frequency and importance of social support received from various significant sources – parents, teachers, classmates and close friends in two groups of adolescents, those with LD and their classmates with average academic achievements.The participants were 188 Lithuanian-speaking adolescents from sixth-seventh grades of Vilnius schools, mean age 12.5 years (SD = 0.7). Ninety-five schoolchildren (64 boys and 31 girls) diagnosed as learning-disabled and 93 schoolchildren (58 boys and 35 girls) comprised an age- and sex-matched comparison group from the same schools with average academic achievements. The participants were assessed on Self-Perception Profile for Children (Harter, 1985) and Child and Adolescent Social Support scales (Malecki et al., 2000). The results revealed that the LD group rated themselves worse than average-achieving students on all domain-specific self-evaluations scales: scholastic competence (t = –5.88, p < 0.001), social acceptance (t = –3.08, p < 0.01) , behavioural conduct competence (t = –2.36, p < 0.05) and global self-evaluation (t = –2.30, p < 0.05). Both groups equally perceived social support, its frequency and importance. There were significant associations between self-evaluations and the perception of social support in both groups. However, there were more significant relationships in the LD group, the perceived importance of social support being significantly related to various self-evaluations among adolescents with LD only (correlations for the LD group ranged from 0.24 to 0.40). The further ANCOVA analysis revealed that the self-evaluation of adolescents with LD, who perceived social support as unimportant, tended to be lower than the self-evaluations of adolescents without LD who disvalued the importance of social support.
Keywords: learning disability; social support; self-evaluation; adolescents